Validation of the Munich Actimetry Sleep Detection Algorithm for estimating sleep-wake patterns from activity recordings - Loock, Ann-Sophie (2021)
© 2021 The Authors. Journal of Sleep Research published by John Wiley & Sons Ltd on behalf of European Sleep Research Society. This is an open access article under the terms of the Creative Commons Attribution‐NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.